2023
DOI: 10.1021/acsami.3c05990
|View full text |Cite
|
Sign up to set email alerts
|

Design, Preparation, and High Intrinsic Proton Conductivity of Two Highly Stable Hydrazone-Linked Covalent Organic Frameworks

Abstract: Assembling crystalline materials with high stability and high proton conductivity as a potential alternative to the Nafion membrane is a challenging topic in the field of energy materials. Herein, we concentrated on the creation and preparation of hydrazone-linked COFs with super-high stability to explore their proton conduction. Fortunately, two hydrazone-linked COFs, TpBth and TaBth, were solvothermally prepared by using benzene-1,3,5-tricarbohydrazide (Bth), 2,4,6-trihydroxy-benzene-1,3,5tricarbaldehyde (Tp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Porous polyoxometalates have garnered significant attention owing to their diverse structures, abundant terminal and bridging oxygen, and large pore sizes. Polyoxovanadates (POVs) represent a significant subclass of POMs and are widely applied in various fields such as proton conductors, magnetism, ion batteries, and catalysts. Notably, vanadium exhibits multiple valence states and presents diverse coordination modes, such as {VO 4 } in a tetrahedral configuration, {VO 5 } in a pentahedral configuration, and {VO 6 } in an octahedral configuration. Introducing the Brønsted acid group as a means to construct POMs is recognized as one of the strategies for enhancing proton conduction performance. , In 2012, Shimizu replaced sulfonate with phosphate to obtain a homogeneous three-dimensional (3D) MOF, and the proton conduction rate was improved to 2.1 × 10 –2 S·cm –1 at 85 °C and 90% RH . In 2020, the Tiemann group compared two 3D Ba 2+ -based MOFs and found that TMOF-2 with –SO 3 H had higher proton conduction due to the hydrophilicity of sulfonate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porous polyoxometalates have garnered significant attention owing to their diverse structures, abundant terminal and bridging oxygen, and large pore sizes. Polyoxovanadates (POVs) represent a significant subclass of POMs and are widely applied in various fields such as proton conductors, magnetism, ion batteries, and catalysts. Notably, vanadium exhibits multiple valence states and presents diverse coordination modes, such as {VO 4 } in a tetrahedral configuration, {VO 5 } in a pentahedral configuration, and {VO 6 } in an octahedral configuration. Introducing the Brønsted acid group as a means to construct POMs is recognized as one of the strategies for enhancing proton conduction performance. , In 2012, Shimizu replaced sulfonate with phosphate to obtain a homogeneous three-dimensional (3D) MOF, and the proton conduction rate was improved to 2.1 × 10 –2 S·cm –1 at 85 °C and 90% RH . In 2020, the Tiemann group compared two 3D Ba 2+ -based MOFs and found that TMOF-2 with –SO 3 H had higher proton conduction due to the hydrophilicity of sulfonate .…”
Section: Introductionmentioning
confidence: 99%
“…24−27 Introducing the Brønsted acid group as a means to construct POMs is recognized as one of the strategies for enhancing proton conduction performance. 28,29 In 2012, Shimizu replaced sulfonate with phosphate to obtain a homogeneous threedimensional (3D) MOF, and the proton conduction rate was improved to 2.1 × 10 −2 S•cm −1 at 85 °C and 90% RH. 30 In 2020, the Tiemann group compared two 3D Ba 2+ -based MOFs and found that TMOF-2 with −SO 3 H had higher proton conduction due to the hydrophilicity of sulfonate.…”
Section: ■ Introductionmentioning
confidence: 99%